A Pyroptosis-Related Gene Panel in Prognosis Prediction and Immune Microenvironment of Human Endometrial Cancer - Zhang, Xiaocui; Yang, Qing (Frontiers in Cell and Developmental Biology, 2021)
As the second common diagnosed cancer among gynecological tumors, endometrial cancer (EC) has heterogeneous pathogenesis and clinical manifestations. Therefore, prognosis predicting considering the gene expression value and clinical characteristics is helpful work to patients with EC. We downloaded RNA expression and clinical data in TCGA database. We got 4 DEPRGs and constructed the PRG panel by univariate Cox analysis. Based on the median value of the risk score, patients were divided into two groups. The Kaplan–Meier curve suggested that the patients with lower risk scores had better clinical outcomes of EC. AUC of ROC curves suggested the panel can be used as an independent predictor. Future analysis indicated the positive correlations between risk score and clinical characteristics. Finally, we performed GO and KEGG functional analysis and immune environment exploration to get an understanding of the potential molecular mechanism and immunotherapeutic target. All in all, we identified a PRG panel to predict the prognosis and immune microenvironment in human EC.